Efektivitas Media Pembelajaran Wordwall Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPAS di SD N 1 Piji - adisti, tria; Amalia Rahmawati, Deki Wibowo, Yoga Awalludin Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of Wordwall learning media on student learning outcomes in the subject of Science at SDN 1 Piji. This study uses a quantitative approach with a quasi-experimental model. The subjects of the study consisted of 29 fifth grade students who were divided into two groups, namely 16 students in the experimental class and 13 students in the control class. Data collection techniques used tests (pretest and posttest), observation, interviews, and questionnaires. The results of the study showed that Wordwall media had a significant effect on improving student learning outcomes. This was proven through the Independent Sample T-Test with a significance value (2-tailed) <0.05. In addition, the results of the Paired Sample T-Test also showed a significance value <0.05, and the N-Gain test showed an average N-Gain score of the experimental class of 79.34%, which was included in the effective category. Student responses to the use of Wordwall media were also positive, where 12 students stated that they liked and 4 students were interested in the media. Thus, it can be concluded that the Wordwall learning media is effective in improving student learning outcomes in the science subject at SDN 1 Piji.